Aage Henriksen: Gotisk tid - Michelsen, William (Grundtvig-studier, 1971)
Aage Henriksen, Gotisk tid. Fire litterære afhandlinger. 1971 Reviewed by William Michelsen This collection of essays is introduced by a study on Grundtvig’s controversy with Baggesen, 1815- 17, which originally appeared in the journal Kritik (vol. I, nos. 1- 2 ) 1967. To a greater or lesser extent, however, Grundtvig is discussed also in the three other essays, especially in the essay on Martin A. Hansen, which is one of professor Aage Henriksen’s weightiest contributions to Danish literary scholarship. In this essay it is claimed that, like Baggesen and Grundtvig, the author of Orm og tyr had a double conception of the figure of Odin. The one Grundtvig calls ‘ Odan the Righteous’ (the poem ‘ Afbrudte Strøtanker’ 1816), the other Aage Henriksen calls ‘ Odin, Loke’s ally’. The idea occurs already in Baggesen’s early poem ‘ Poesiens Oprindelse’. Aage Henriksen disagrees with Ole Wivel’s opinion that in the last part of his works Martin A. Hansen was in favour of the division between religion and social life that, in Denmark, is known as secularisation; on the contrary, ‘from 1940 to 1955 his works, including the essays, are of a religious nature’. He regarded Luther, Kant, and Kierkegaard as stages on a way that he sometimes called ‘secularisation’, sometimes ‘the way of the personality’, and the purpose of which was that of breaking down any ideology. Aage Henriksen holds that Martin A. Hansen’s conception of ‘secularisation’ is different from Wivel’s. In his essay ‘ Leviathan’, Martin A. Hansen looked upon Grundtvig as ‘the innovator after the three others . . . he reaches beyond Protestantism, and in him we begin to see the embryo of a new culture’. But Martin A. Hansen could see no more than the faint outlines of this new culture, like Paradise from which he was separated by the Cherub. Aage Henriksen phrases it like this, ‘unlike Grundtvig he was not able to integrate the art of dying into the art of living.’ This expression stems from Aage Henriksen’s interpretation of ‘ Nyaars- Morgen’, which is incorporated in the Baggesen study. The poem falls into three parts, the first of which is a dream, the second an inspiration with Divine love, and the third a renunciation of the poet’s own life. The main character casts off his slough, and the last sloughing is ‘the art of dying’. He finds instances of this in a number of Danish novels representing the development of personality and—in the Gospel according to St. John, read as if it were a short story. But his point of departure is the mutual understanding he has shown to exist between Grundtvig and Baggesen.